telescoping sum
A telescoping sum is a sum in which cancellation occurs between subsequent terms, allowing the sum to be expressed using only the initial and final terms.
Formally a telescoping sum is or can be rewritten in the form
S=β∑n=α(an-an+1)=aα-aβ+1 |
where an is a sequence.
Example:
Define S(N)=∑Nn=11n(n+1). Note that by partial fractions of expressions:
1n(n+1)=1n-1n+1 |
and thus an=1n in this example.
S(N)=N∑n=1(1n-1n+1) |
=(1-12)+⋯+(1n-1n+1)+(1n+1-1n+2)+⋯+(1N-1N+1) |
=1+(-12+12)+⋯+(-1n+1+1n+1)+⋯-1N+1 |
=1-1N+1 |
Title | telescoping sum |
---|---|
Canonical name | TelescopingSum |
Date of creation | 2013-03-22 14:25:18 |
Last modified on | 2013-03-22 14:25:18 |
Owner | cvalente (11260) |
Last modified by | cvalente (11260) |
Numerical id | 8 |
Author | cvalente (11260) |
Entry type | Definition |
Classification | msc 40A05 |
Defines | telescope |